Kinerja Pegawai pada Kegiatan Bongkar Muat Kargo Pembangkit Listrik Tenaga Uap Sumatera Selatan - Rasidi, Fazar Iman; Suparman, Asep; Pahala, Yosi; Fachrial, Peppy; Adi, Erman Noor (Institut Transportasi dan Logistik Trisakti, 2023)
The loading and unloading company is partner for the loading and unloading cargo process at the port. Many loading and unloading companies, large and small, in Jetty Patratani, Indralaya, South Sumatra Province, cooperate to support the process smoothly. The cooperation process should give optimal performance. In this study, the employees’ performance is measured by discipline as the character and skills in carrying out the loading and unloading activities. The aim of the study is to find out the effect of discipline and skills on the employees’ performance of PT. Solid Shipping Indonesia. The study used Quantitative research methods with a cross-sectional research design. The population was all employees of the company, 152 people, with a 110 sample based on Slovin formula calculation. The data analysis technique was using multiple linear regression. The results show that, partially, the discipline variable has a positive and significant effect on employees’ performance, the skill variable, partially, has a positive and significant effect on employees’ performance, and simultaneously, the discipline and skill variables have a positive and significant effect on employees’ performance.